Potential employment of transcranial magnetic stimulation as a beneficial intervention in children with amblyopia: a brief overview - Indra Tri Mahayana; Dhimas Hari Sakti; Natalia Christina Angsana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Amblyopia is an early functional imbalance between each eye and the brain that may result in visual cortex inhibition. Current conservative treatments involve altering the input from the ‘good eye’, for example, using patching or biochemical penalization. Direct brain stimulation to the amblyopic cortex might improve the condition. This paper aimed to systematically review the published scientific literature regarding the use of transcranial magnetic stimulation (TMS) as a potential method for treatment in the amblyopic visual cortex. This study was a systematic review of the published scientific literature related to theTMS for the treatment of amblyopia that was performed using “TMS, amblyopia” as keywords. However, only three research papers were found and included in the literature review. A study showed that repetitive TMS of the visual cortex can temporarily improve contrast sensitivity in the amblyopic visual cortex. Another study used continuous thetaburst stimulation (cTBS) delivered to the visual cortex while patients viewed a high contrast stimulus with their non-amblyopic eye. It was found that daily theta burst TMS stimulation improved amblyopic eye contrast sensitivity in five adult volunteers. The TMS also increased median visual acuity in the patient with amblyopia after stimulation with no significant changes in the placebo group.Protocol employing repetitive administration of TMS might result in beneficial effects in amblyopia treatment. TMS works in brain dynamics and experience-dependent plasticity, all of which could be important in investigating and treating amblyopia.